New measures to assess the "Other" three pillars of food security-availability, utilization, and stability - Eric E. Calloway; Leah R. Carpenter; Tony Gargano; Julia L. Sharp; Amy L. Yaroch (BMC, 2023)
Abstract Background In recent reviews of available measures, no existing measures assessed all four pillars of food security and most only assessed one or two pillars-predominantly the access pillar. The purpose of this study was to preliminarily develop novel measures of availability, utilization, and stability that are complementary to the USDA's household food security survey measure (HFSSM). Methods A formative phase included an expert advisory group, literature scans, and interviews with individuals experiencing food insecurity. From April-June 2021, the new measures were piloted in five states (California, Florida, Maryland, North Carolina, and Washington). The cross-sectional pilot survey included the new measures (perceived limited availability, utilization barriers, and food insecurity stability), scales and items for validation (e.g., food security, and self-reported dietary and health outcomes), and demographic questions. Exploratory factor analysis was used to assess dimensionality, internal consistency was assessed using Kuder-Richardson formula 21 (KR21), and convergent and discriminant validity were assessed using Spearman's correlation coefficients. Also, a brief screener version was created for the utilization barriers measure that may be necessary for certain applications (e.g., clinical intake screening to inform referrals to assistance programs). Results The analytic samples (perceived limited availability (n = 334); utilization barriers (n = 428); food insecurity stability (n = 445)) were around 45 years old on average, most households had children, over two-thirds were food insecure, over three-fourths were women, and the samples were racially/ethnically diverse. All items loaded highly and unambiguously to a factor (factor loadings range 0.525-0.903). Food insecurity stability showed a four-factor structure, utilization barriers showed a two-factor structure, and perceived limited availability showed a two-factor structure. KR21 metrics ranged from 0.72 to 0.84. Higher scores for the new measures were generally associated with increased food insecurity (rhos = 0.248-0.497), except for one of the food insecurity stability scores. Also, several of the measures were associated with statistically significantly worse health and dietary outcomes. Conclusions The findings support the reliability and construct validity of these new measures within a largely low-income and food insecure sample of households in the United States. Following further testing, such as Confirmatory Factor Analysis in future samples, these measures may be used in various applications to promote a more comprehensive understanding of the food insecurity experience. Such work can help inform novel intervention approaches to address food insecurity more fully.